2013
DOI: 10.1093/qjmed/hct159
|View full text |Cite
|
Sign up to set email alerts
|

The connected health of cardiovascular medicine: current status and future directions

Abstract: The technologies of cardiovascular connected health stand to dramatically alter the management and prevention of cardiovascular disease, a worldwide leading cause of death. The American Heart Association has outlined seven key health metrics including physical activity, adequate blood pressure control, weight and a healthy diet, which lie at the core of cardiovascular disease management. Controlling these metrics has been demonstrated to result in substantial reductions in cardiovascular mortality. These metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…mHealth can improve blood pressure control by enhancing patient awareness in self‐management and strengthening communication between healthcare providers and patients 31,32 . A previous meta‐analysis has reported the benefit of mHealth on blood pressure management in the general hypertensive population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mHealth can improve blood pressure control by enhancing patient awareness in self‐management and strengthening communication between healthcare providers and patients 31,32 . A previous meta‐analysis has reported the benefit of mHealth on blood pressure management in the general hypertensive population.…”
Section: Discussionmentioning
confidence: 99%
“…30 mHealth can improve blood pressure control by enhancing patient awareness in self-management and strengthening communication between healthcare providers and patients. 31,32 A previous metaanalysis has reported the benefit of mHealth on blood pressure management in the general hypertensive population. Its subgroup analysis demonstrated that the effect size tended to be more prominent in those with baseline uncontrolled hypertension, 33 Morawski and coworkers has reported that mHealth management had no significant benefit in systolic blood pressure control and only had improvement in self-reported adherence.…”
Section: Number Of Comparisons Wmd (95% Ci) P P For Interactionmentioning
confidence: 99%
“…One of the areas of concern that Connected Health will have impact, besides caring for the aged (such as in [42]), is in the management of chronic diseases [6]. As a result, many researchers working on Connected Health are already testing the relevance and applicability of connected health in the management of chronic diseases such as cardiovascular disease [7] and dementia [18]. In confirming the practical applicability of Connected Health [41] reported a project which produced WIISEL (Wireless Insole for Independent and Safe Elderly Living) system, designed to monitor fall risk and to detect falls in older people [42].…”
Section: A Connected Healthmentioning
confidence: 99%
“…With further time for patient recall, the intervention lag could range from 2–5 days. The delay could be reduced with telephone follow‐up and use of recent advances in telemonitoring of clinical symptoms and signs . Taking this intervention lag into account is essential in planning a monitoring schedule.…”
Section: Limitations Of Monitoring Renal Functionmentioning
confidence: 99%